THE INCREASING OF HUMAN RESOURCE QUALITY THROUGH TRAINING AND ITS EFFECT ON RAISING INCOME - harini, sri (Universitas Djuanda, 2015)
The important roles of micro business / SME’s on Indonesian economic environment are the labor absorption, income increases and society welfare. But, in the other hand several weaknesses have become resistor factors for the growth of the micro business, especially quality of the human resources. The enhancement of human resource quality through training needed to increase the competitive advantage of micro business to achieve a larger scale of business, by work a better management, using natural and safety dye for food coloring and involvement in creating a healthy business. Kind of training conducted are management training, entrepreneurship, making natural food dye and waste management. The research aims to figure out the effect of training toward income. Research method is qualitative descriptive. Data collection conducted by questioner, interview and observation. Data analysis method using regression analysis, determination coefficient, and hypothesis test. The result shows that training affect significantly toward income, training has contributed toward increasing income. If enhancement of human resource quality tends to be better, then business revenue will increase.